The invention of Sophie Carter - Hastings, Samantha (Swoon Reads, 2020)
In 1851 London identical twin sisters take turns swapping places over the course of a summer in order to pursue their secret ambitions, but things get out of control when they fall in love with two hansome gentlemen.